Modeling and validation of brushless DC motor - Mohd Sabri, Hussin; Azuwir, Mohd Nor; Nor Zaiazmin, Yahaya (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/